(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2014)
Serological and entomological surveys were conducted to establish the prevalence of Chagas disease, the vector presence, and the trypan triatomine index in the school population of Juan Gómez Rendón Parish, in the Province of Guayas, Ecuador. To detect reactives, blood samples from students of 12 schools were processed using ELISA, confirmatory testing by ELISA (enzyme immunoassay test for the detection of anti Trypanosoma cruzi antibodies) + HAI (indirect hemagglutination) were performed at the Institute of Public Health and Research. Were analized 1.967 samples, 23 of those were reactive and eight cases were confirmed. A total of 1.831 houses were inspected at intra and peridomestic levels in six localities, 8.702 triatomine were captured, those were identified as Triatoma dimidiata in the area of entomology at the National Service of Malaria Control (SNEM). The vector presence has been detected in five of those six localities, the vector infestation index ranged from 10.2 to 33.9%, and the colonization varies from 62 to 91.9%. A total number of 5.650 triatomines were examined microscopically, 2.170 of those were naturally infected having a triatomine tripan index of 38.4%. The Chagas disease affects the population younger than 15 years old in four of the 12 studied schools, Triatoma dimidiata has been identified as the vector.